2010
DOI: 10.1124/dmd.109.031476
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism and Disposition of the Oral Dipeptidyl Peptidase-4 Inhibitor, Linagliptin, in Humans

Abstract: ABSTRACT:The pharmacokinetics and metabolism of linagliptin (BI1356, 8-(3R-amino-piperidin-1-yl)-7-but-2-ynyl-3-methyl-1-(4-methylquinazolin-2-ylmethyl)-3,7-dihydro-purine-2,6-dione) were investigated in healthy volunteers. Type 2 diabetes mellitus (T2DM) accounts for 90 to 95% of all diabetes cases and its incidence is increasing (Wild et al., 2004). The high frequency of complications associated with the disease leads to a significant reduction in life expectancy. One relatively new therapeutic option is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(166 citation statements)
references
References 33 publications
3
162
0
1
Order By: Relevance
“…Fecal excretion was the dominant excretion pathway with 84.7% and 58.2% of the dose, while renal excretion accounted for 5.4% and 30.8% of the dose, after oral and intravenous administration, respectively. Several metabolites were identified but it was concluded that they only play a minor role in the overall disposition and elimination of the drug 67 . A single rising-dose, randomized, four-group, placebo-controlled study was performed in healthy men to investigate PK and PD of linagliptin after intravenous administration (0.5 mg, 2.5 mg, 10 mg) and to determine the absolute bioavailability of the drug (comparison between 5 mg intravenous and 10 mg oral administration) 68 .…”
Section: Healthy Volunteersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecal excretion was the dominant excretion pathway with 84.7% and 58.2% of the dose, while renal excretion accounted for 5.4% and 30.8% of the dose, after oral and intravenous administration, respectively. Several metabolites were identified but it was concluded that they only play a minor role in the overall disposition and elimination of the drug 67 . A single rising-dose, randomized, four-group, placebo-controlled study was performed in healthy men to investigate PK and PD of linagliptin after intravenous administration (0.5 mg, 2.5 mg, 10 mg) and to determine the absolute bioavailability of the drug (comparison between 5 mg intravenous and 10 mg oral administration) 68 .…”
Section: Healthy Volunteersmentioning
confidence: 99%
“…The fraction of dose excreted unchanged in urine was dose-dependent and increased from below 1% in the 5 mg group up to about 33% in the 600 mg group. The PK and metabolism of linagliptin were investigated further in healthy volunteers 67 . The 10-and 5-mg 14 C-labeled drug was administered orally or intravenously, respectively.…”
Section: Healthy Volunteersmentioning
confidence: 99%
“…Despite the renal excretion profiles of these agents, their favorable tolerability in patients with various severity of renal dysfunction still permits their use in such patients, although dose modifications are recommended in line with increasing kidney dysfunction ( Table 2). In contrast, linagliptin is excreted through the bile and with approximately 5% being renally excreted 80 . Furthermore, recent data suggest that dose modifications of linagliptin are not required irrespective of the severity of renal dysfunction (Table 2) 81 .…”
Section: Current Oral Anti-diabetics In Diabetic Patients With Ckdmentioning
confidence: 99%
“…Management of T2DM in renal impairment is challenging as treatment options are limited, and the majority of the therapeutic agents are either contraindicated or not recommended in moderate to severe renal impairment. Linagliptin is the only DPP-4 inhibitor that has a primarily nonrenal route of excretion, 25 while 90 per cent of sitagliptin and 22 per cent of vildagliptin is excreted unchanged via the kidney. Thus, it offers a potential therapeutic option in the management of T2DM patients with renal impairment.…”
Section: Renal Acceptabilitymentioning
confidence: 99%